Identification of Long Noncoding RNA APOC1P1 as an Oncogene in Clear Cell Renal Cell Carcinoma. (1st December 2019) - Sun, Chong; Zhou, Zhonghan; Shi, Haoqing; Li, Fangzhou; Zhang, Guiming
Abstract : Renal cell carcinoma (RCC) is one of the most common genitourinary cancers worldwide. Previous evidence shows that long noncoding RNA (LncRNA) APOC1P1 plays an important role in cancer development. However, the role of LncRNA APOC1P1 in ccRCC remains to be explored. LncRNA APOC1P1 expression in 283 ccRCC tissues and 30 normal kidney tissues was detected by quantitative real-time PCR, and its prognostic association with ccRCC was assessed by the Kaplan-Meier method and Cox proportional hazard model. Cell proliferation, apoptosis, migration, and invasion were determined in RCC cells with downregulation of LncRNA APOC1P1 expression. LncRNA APOC1P1 expression was increased in ccRCC tissues compared with normal kidney tissues (P < 0.001 ). Its expression was higher in the Fuhrman grade III and IV group than in the Fuhrman grade I and II group (P < 0.05 ) and significantly upregulated in the advanced stage group (P < 0.05 ). Kaplan-Meier analyses revealed that elevated LncRNA APOC1P1 expression was significantly associated with poor overall survival (P < 0.05 ) but may not be an independent prognostic factor. Knockdown of LncRNA APOC1P1 inhibited cell proliferation, induced apoptosis, and arrested cells at the G1/S phase (P < 0.05 ). Silencing of LncRNA APOC1P1 also led to decreased cell migration and invasion (P < 0.05 ). LncRNA APOC1P1 acts as an oncogene, plays an important role in ccRCC development, and can be considered a prognostic biomarker and therapeutic target in ccRCC patients.